Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The Ideological and Strategic Dimensions of American Support for Israel During the Gaza War Mr. Akram Mohammad Ali Chamas 2. Methods for enhancing AI applications in improving schedule and resource management in agile infrastructure projects in KSA Dr. Anwar Mohammed Gismallah Mohammed 3. The Guarantees of the Public Employee in the Administrative Investigation (A Comparative Study between the Saudi System and the Egyptian Law) Ms. Dareen Yousef Al-Thaqafi 4. The Impact of the University Education (Research) index on the Global Competitiveness of the United Arab Emirates During the Period (2021-2022) Dr. Shawk Hasan Mahdi 5. The Impact of Digital Transformation on Governance Principles at the Royal Oman Police from the Perspective of External Stakeholders Dr. Azza Said Hilal Al-Sharji, Dr. Khalifa Mohammed Said Al-Fathi 6. Human resource management (HRM) practices and employee job satisfaction: The case of a public corporation in Qatar Ms. Baina Hamad Al-Marri 7. Assessing the impact of AI influencers on customer engagement for non-luxury brands in Egypt Ms. Nesma Ibrahim Amir Abdelrazek, Ms. Alaa Tarek Khalil